2005
DOI: 10.1080/10826070500189737
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Identification of Eight Hydrophilic Vitamins Using a New TLC Method and Raman Spectroscopy

Abstract: Hydrophilic vitamins play an important role in human health. The analysis of these compounds is indispensable for monitoring their content in pharmaceuticals and food in order to prevent some human diseases. The separation and identification of eight hydrophilic vitamins, i.e., B 1 , B 2 , B 3 , B 5 , B 6 , B 9 , B 12 , and C, was achieved by thin layer chromatography and Raman spectrometry. After chromatographic experiments, the best results were obtained using programmed multiple development. The unambiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…37 In a recent study reported by our research group, Ilaslan et al used Raman spectroscopy to quantify glucose, fructose and sucrose contents of commercial so drinks. 80 The use of Raman microscopy also made it possible to determine and localize vitamins in biological samples. The calibration curves were obtained for each component by applying PLS regression on Raman data, and validation studies were carried out using HPLC.…”
Section: Proteinsmentioning
confidence: 99%
“…37 In a recent study reported by our research group, Ilaslan et al used Raman spectroscopy to quantify glucose, fructose and sucrose contents of commercial so drinks. 80 The use of Raman microscopy also made it possible to determine and localize vitamins in biological samples. The calibration curves were obtained for each component by applying PLS regression on Raman data, and validation studies were carried out using HPLC.…”
Section: Proteinsmentioning
confidence: 99%
“…Strong bands at 1,650.79 and 1,630.4 cm (1 in Raman and IR spectra could be attributed to the C 0C stretching vibration, as observed in the FT Raman spectrum of six vegetable oils containing palmitic acid as one of the major constituents (Muik et al 2005). The C 0C stretching vibration could also be attributed to the strong Raman band at 1,598.12 cm (1 , as assigned in the Raman spectrum for nicotinic acid (Cimpoiu et al 2005). The O ÃH bond appears to give a deformation vibration at around 1,410 cm (1 , correlating to that seen in the FTIR spectrum of water-soluble vitamin B compounds (Li and Brown 2003).…”
Section: Resultsmentioning
confidence: 84%
“…The infrared spectrum of chilli seeds presented in Figure 4 clearly shows the presence of the vibrational bands of palmitic acid, namely the CH 2 stretching bands at 2,930 and 2,854 cm (1 , the C 0C stretching vibration as a shoulder at (approximately) 1,650 cm (1 , the CH 2 scissors deformation at 1,464 cm (1 and the fatty acid chain consisting of weak bands from 1,280 to 1,040 cm (1 . Raman bands at 3,077.88 cm (1 (the lack of sufficient strength is the cause of indecisiveness), 1,598.12 cm (1 and 800 cm (1 could be correlated with those for nicotinic acid (Cimpoiu et al 2005). But the most significant finding is the absence of ascorbic acid in the seeds, whose amount at 63.70 mg/100 g has been the maximum among the vitamins present in chillies (Pruthi 2003).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations